OPTIMASI VALUE AT RISK REKSA DANA MENGGUNAKAN METODE ROBUST EXPONENTIALLY WEIGHTED MOVING AVERAGE (ROBUST EWMA) DENGAN PROSEDUR VOLATILITY UPDATING HULL AND WHITE - Khalida Hanum; Tarno Tarno; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
Risk measurement is important in making investments. One tool to measure risk is Value at Risk (VaR), which is the worst possible loss on a given time horizon under normal market conditions with a certain confidence level. The successful implementation of VaR depends on conditional volatility estimates of portfolio returns. Robust Exponentially Weighted Moving Average (robust EWMA) is one approach in forecasting the conditional volatility of asset returns. Robust EWMA is suitable for financial data analysis which is heteroscedastic and not normally distributed. The final VaR is calculated using historical simulation method with updated data return through volatility updating Hull and White procedure. In this research, robust EWMA is used for portfolio VaR calculation with case study of mutual funds shares BNI AM Dana Berkembang (BNI), Manulife Dana Saham Utama (MDSU) and Mega Asset Greater Infrastructure (MAGI). Validity testing of VaR was conducted based on Basel rule and Kupiec's proportion of failures (PF) test. The result of backtesting test shows that the obtained VaR are valid to predict the loss of the equity fund portfolio at both 95% and 99% confidence level.Keywords : mutual fund, Value at Risk, robust EWMA, volatility updating